Multi-stage Holocene evolution of the River Murray Estuary, South Australia. (January 2021) - Job, Thomas; Penny, Dan; Morgan, Bree; Hua, Quan; Gadd, Patricia; Zawadzki, Atun
The River Murray Estuary, South Australia exhibits a morphology typical of a wave-dominated estuary and comprises two large, shallow central basin lakes – Lakes Alexandrina and Albert. Contested interpretations of the estuary's limnological history and uncertainty surrounding the sustainability of current basin water usage practice warrant a robust investigation into how the system has evolved. Here we combine lithostratigraphic, geochemical and sedimentological evidence from a transect of sediment cores to reconstruct the sediment infill history of the system. We uncover multiple stages of sediment infill over the history of the system, associated with (1) the low gradient morphology of the estuary and lower river channel, (2) the mid- to late-Holocene sea-level regression and (3) anthropogenic modifications to the fluvio-estuarine system. We show that while estuarine conditions in the system were fully established during the mid-Holocene highstand ( 6.4 kyr BP), central basin facies sedimentation was focussed further inland before prograding with the lowering of base level and shifting of tidal influence as sea-level fell. Central basin facies sedimentation within northern Lake Albert occurred from 5.4 to 4.0 cal kyr BP at 0.25 cm yr -1 . The uppermost accumulation of this unit was eroded by continued reduction in base level until sea-level regression concluded at 3.5 cal kyr BP. Barrage and weir installation (1940 CE) re-initiated and expanded central basin facies sedimentation in the estuary ( 0.32 cm yr -1 ). Recently deposited sediments exhibit geochemical markers of increased trophy and more frequent acid sulfate soil acidification, exposing human impacts on the estuary.